Designing an operating theatre for awake procedures: A solution to improve multimodality information input. (2nd November 2015) - Wager, Michel; Rigoard, Philippe; Bataille, Benoit; Guenot, Claude; Supiot, Aurélie; Blanc, Jean-Luc; Stal, Veronique; Pluchon, Claudette; Bouyer, Coline; Gil, Roger; Du Boisgueheneuc, Foucaud
Abstract : Objective . Many neurosurgical procedures are now performed with the patient aware in order to allow interactions between the patient and healthcare professionals. These procedures include awake brain surgery and spinal cord stimulation (SCS), lead placement for treatment of refractory chronic back and leg pain. Neurosurgical procedures under local anaesthesia require optimal intraoperative cooperation of the patient and all personnel involved in surgery. In addition to accommodating this extra source of intraoperative information all other necessary sources of data relevant to the procedure must be presented. The concept of an operating room dedicated to neurosurgical procedures performed aware and accommodating these concepts is presented, and some evidence for improvements in outcome presented, deriving from a series of patients implanted with spinal cord stimulators before and after the operating theatre was brought into service. Results and discussion . In addition to the description, two videos demonstrate the facility online. Beyond this qualitative evidence, quantitative improvement in patient outcome is evidenced by the series presented: 91.3% of patients operated in the awake anaesthesia-dedicated theatre obtained adequate low back pain coverage, versus 60.0% for patients operated before (p = 0.028). Conclusion . The concept of such an operating room is a step in improving the outcome by improving the presentation of all types of information to the operating room staff most notably in the example of aware procedures.